Isu-isu sokongan sosial dalam kalangan kanak-kanak mangsa penderaan seksual di institusi pemeliharaan dan perlindungan - Abd Manaf, Abdul Razak; Mokhtar, Norliza (Universiti Tun Hussein Onn Malaysia, 2016)
Sexual abuse among children is seen as a phenomenon that is of deep concern.These victims,who are placed in welfare institutions, are always the center of attention of the citizens due to what they have experienced.The objective of this paper is to examine several social support issues that were shared by victims of sexual abuse placed under government welfare institutions. Eight girls were chosen to participate in a focused group discussion.The results of this qualitative study produced a number of social support issues that should be refined by the stakeholder.One of the pressing issues is the difficulty to obtain the needed social support. Besides that, inconsistent social support services given by the staff at the institution also caused some dissatisfaction among the children.The members in the focused group discussion also shared their form of demanded social support while they are staying in the institution.The implication of the study was also discussed.